No official identity: a data linkage study of birth registration of Aboriginal children in Western Australia. (3rd July 2016) - Gibberd, Alison J.; Simpson, Judy M.; Eades, Sandra J.
Abstract: Objective : Evidence of identity, particularly a birth certificate, is essential to access many rights. However, the births of many Aboriginal Australians are not registered when they are infants. We examined factors related to birth registration among Western Australian children born to Aboriginal mothers. Methods : All births to Aboriginal mothers in the Midwives Notification System in Western Australia (WA) from 1980 to 2010 were linked to birth registrations. Associations between registration and maternal and child characteristics were examined for children aged under 16 years in 2012. Results : Among 49, 694 births between 1980 and 2010, 18% of those aged under 16 years had unregistered births, compared to 3% of those aged 16–32 years. Unregistered births were most strongly associated with young maternal age at first birth (adjusted odds ratio [AOR] 5.22; 95%CI 3.07–8.86; for 16 years or younger vs 30 years or older, among non‐smokers), remoteness (AOR 2.17; 95%CI 1.87–2.52; very remote vs major cities), mothers whose own birth was unregistered (AOR 3.00; 95%CI 1.78–5.07) and no private hospital insurance (AOR 0.19; 95%CI 0.11–0.31; insured vs uninsured). Conclusions : Unregistered births are common among WA Aboriginal children, particularly in disadvantaged families. Implications : Assistance before discharge from hospital may increase birth registrations.